Evaluation of the Cortisol‐to‐ACTH Ratio in Dogs with Hypoadrenocorticism, Dogs with Diseases Mimicking Hypoadrenocorticism and in Healthy Dogs. (6th August 2015) - Boretti, F.S.; Meyer, F.; Burkhardt, W.A.; Riond, B.; Hofmann‐Lehmann, R.; Reusch, C.E.; Sieber‐Ruckstuhl, N.S.
<x xml:space="preserve">Abstract</x> Background The adrenocorticotropic hormone (ACTH) stimulation test is the gold standard for diagnosing hypoadrenocorticism (HA) in dogs. However, problems with the availability of synthetic ACTH (tetracosactrin/cosyntropin) and increased costs have prompted the need for alternative methods. Objectives To prospectively evaluate the cortisol‐to‐ACTH ratio (CAR) as a screening test for diagnosing canine HA. Animals Twenty three dogs with newly diagnosed HA; 79 dogs with diseases mimicking HA; 30 healthy dogs. Methods Plasma ACTH and baseline cortisol concentrations were measured before IV administration of 5 μg/kg ACTH in all dogs. CAR was calculated and the diagnostic performance of ACTH, baseline cortisol, CAR and sodium‐to‐potassium ratios (SPRs) was assessed based on receiver operating characteristics (ROC) curves calculating the area under the ROC curve. Results The CAR was significantly lower in dogs with HA compared to that in healthy dogs and in those with diseases mimicking HA (P < .0001). There was an overlap between HA dogs and those with HA mimicking diseases, but CAR still was the best parameter for diagnosing HA (ROC AUC 0.998), followed by the ACTH concentration (ROC AUC 0.97), baseline cortisol concentration (ROC AUC 0.96), and SPR (ROC AUC 0.86). With a CAR of >0.01 the diagnostic sensitivity and specificity were 100% and 99%, respectively. Conclusion and Clinical Importance Calculation of the CAR is a useful screening test for diagnosing primary HA. As a consequence of the observed overlap between the groups, however, misdiagnosis cannot be completely excluded. Moreover, additional studies are needed to evaluate the diagnostic reliability of CAR in more dogs with secondary HA.